La diglossia nel linguaggio letterario, artistico e museale – Un approccio alla comprensione delle diversità culturali (Muse, 2025)
This article aims to analyze the concept of diglossia, historically linked to the linguistic field, and to extend its applicability to a broader cultural dimension that includes literary, artistic, and, finally, museological language. It is argued that diglossia — understood as the coexistence of different communicative languages and codes within the individual and the community — is not a marginal phenomenon, but an intrinsic and pervasive condition of contemporary life. The essay is based on a research project concerning the historical-artistic context of post-unification Sardinia, where the concept of visual diglossia was introduced. The Sardinian case, with its historical trajectory of local artists mediating between 'native' languages and dominant cultural codes, offers an innovative paradigm for understanding the dialogue between hegemonic and subaltern cultures, anticipating phenomena later extended to Italy and other post-colonial contexts.This visual diglossia, originating in art and reflected in the organizational models of international bodies like ICOM, facilitates the translation between a global exhibition 'language' and local cultural languages. Considering diglossia as a widespread competence in dissemination enables a dynamic process that favors the re-emergence of even peripheral cultural meanings and their access to a wide audience, overcoming spatio-temporal and cultural barriers. In an era of increasing interconnectedness, the ability to manage this diglossia is crucial for transforming museum heritage into a 'shared communication theater,' where cultural diversity is actively mediated.
Keywords: Diglossia; Diglossia Visiva; Linguaggio Museale; Ibridazione Culturale; Post-coloniale; Visual Diglossia; Museological Language; Cultural Hybridization; Post-colonial